Observer effects strongly influence estimates of daily nest survival probability but do not substantially increase rates of nest failure in Greater Sage-Grouse. (18th February 2015) - Gibson, Daniel; Blomberg, Erik J.; Atamian, Michael T.; Sedinger, James S.
Abstract: Researchers have long recognized that the process of observing nests may influence nest success by increasing depredation risk or causing females to abandon nests. The effects of observer-related nest abandonment may also reduce estimates of daily nest survival when time to nest fate is reduced and the average nest exposure period within the sample becomes shorter. We used an 8-yr record of observer visitations of nesting female Greater Sage-Grouse ( Centrocercus urophasianus ) in central Nevada, USA, to assess whether observers influenced either the probability of daily nest survival or the overall probability of nest success. Because nest success is influenced by factors other than visitation, we also accounted for the overall quality of a nest (i.e. probability of success in the absence of observer effects) based on potential confounding factors. Nest visitation (no flushing) had no effect on daily nest survival, regardless of nest quality or female age. Flushing a female from a nest substantially lowered the probability of the nest surviving the following day (maximum 0.22). When considered in the context of the entire nest exposure period, however, flushing a female once produced only a marginal reduction in overall nest success ( 0.015). Additionally, females that were younger, or that were associated with low-quality nests, were more likely to abandon the nest after flushing, compared with older females or those associated with higher-quality nests. Observer-related abandonment, however, introduced a negative bias ( 0.07) into estimates of overall nest survival by reducing the average timing of nest fate and thereby lowering daily nest survival. Our results suggest that the act of flushing female Greater Sage-Grouse may bias estimates of nest survival low, but this is due to an effect on estimates of daily nest survival, rather than an actual influence on the probability of nest fate.